The Central Government's Authority in Spatial Planning - Alfons, Saartje Sarah; Berlianty, Teng; Angga, La Ode (International Journal of Psychosocial Rehabilitation, 2020)
Based on the analysis in writing this article, the answer obtained is that the authority of spatial planning is the authority of the State (central government), the authority of the provincial regional government, and the authority of regency and city regional governments. The authority is divided according to levels of government. The State's authority (central government) in the spatial planning sector provided by the laws and regulations in the context of realizing the State's responsibility (the central government) as the highest power organization that has the authority to control, in the sense of regulating the supply, supply, utilization, and use earth, and water, and the natural wealth contained therein, and space to be used to the maximum prosperity of the people. In this way, order, peace, legal certainty, and social justice will be created as well as benefits as the objectives and functions of law in general, and more specifically in the application of the principle of caution in the field of spatial planning.